2017
DOI: 10.2147/ott.s120440
|View full text |Cite
|
Sign up to set email alerts
|

<em>BRAF</em><sup>V600</sup> mutations in solid tumors, other than metastatic melanoma and papillary thyroid cancer, or multiple myeloma: a screening study

Abstract: BackgroundMutations in the BRAF gene have been implicated in several human cancers. The objective of this screening study was to identify patients with solid tumors (other than metastatic melanoma or papillary thyroid cancer) or multiple myeloma harboring activating BRAFV600 mutations for enrollment in a vemurafenib clinical study.MethodsFormalin-fixed, paraffin-embedded tumor samples were collected and sent to a central laboratory to identify activating BRAFV600 mutations by bidirectional direct Sanger sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 20 publications
2
22
0
3
Order By: Relevance
“…Although this is a great activity for previously treated NSCLC, the addition of a MEK inhibitor (trametinib) was necessary to achieve a significant higher response rate. Cohn et al in 2017 published their results of a multicenter, national screening study for BRAF V600 mutations, which confirmed previously reported incidences of this driver oncogene, and will allow the identification and possible enrollment of patients into the VE-BASKET study [34].…”
mentioning
confidence: 67%
“…Although this is a great activity for previously treated NSCLC, the addition of a MEK inhibitor (trametinib) was necessary to achieve a significant higher response rate. Cohn et al in 2017 published their results of a multicenter, national screening study for BRAF V600 mutations, which confirmed previously reported incidences of this driver oncogene, and will allow the identification and possible enrollment of patients into the VE-BASKET study [34].…”
mentioning
confidence: 67%
“…BRAF mutations are found in 7% of cancers, most commonly in melanoma, papillary thyroid cancer, hairy cell leukemia, and colorectal cancers (21)(22)(23). BRAF mutations are also known to be present in subsets of patients with ovarian, breast, or lung cancers (23)(24)(25)(26). On the basis of the knowledge of oncogenic BRAF mutations, precision cancer therapy using BRAF inhibitors has been tested in different types of cancers.…”
Section: Braf Mutation In Cancermentioning
confidence: 99%
“…An additional challenge is the absent tumor specificity of mutations. For example, mutant BRAF has not only been detected in MM (40–60 %) but also in other malignancies, including hairy cell leukemia (100 % of classic cases) , papillary thyroid cancer (55–67 %) , colorectal cancer (5–10 %) , biliary tract tumors (6 %) , multiple myeloma (5 %) , non‐small cell lung cancer (up to 4 %) and to a lesser extent in lymphoproliferative and myeloproliferative disorders, sarcomas, ependymomas, as well as liver, stomach, esophageal, breast and ovarian cancers . It has also been observed in glioma (10–60 %) , gastrointestinal stromal tumor (GIST) (7 %) and in rare histiocytic disorders such as Erdheim‐Chester disease (54 %) and Langerhans cell histiocytosis (38 %) .…”
Section: Limitations Of Liquid Biopsy In Routine Diagnosticsmentioning
confidence: 99%